2021
DOI: 10.1007/s10120-021-01163-y
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of p53 protein overexpression on the survival of gastric cancer patients according to Lauren histologic classification: a retrospective study

Abstract: Background Inactivation of TP53, a tumor suppressor gene, is associated with the development of several malignancies, including gastric cancer (GC). The present study aimed to evaluate the correlation between the overexpression of p53 and survival in different Lauren-type GCs. Methods From May 2003 to December 2019, 3608 GC patients treated endoscopically or surgically at the Seoul National University Bundang Hospital were enrolled for the study. Immunohistochemical staining for p53 was performed on all endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…The pattern of P53 overexpression also differed by sex; P53 overexpression was more frequent in males and intestinal-type GC patients. In our previous report on P53 overexpression, the clinical and prognostic significance differed by histological type of GC; P53 overexpression was more common in intestinal-type GC, but was associated with a poor prognosis for diffuse-type GC[ 18 ]. Therefore, it is also likely to act as a factor that affects GC prognosis differently in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of P53 overexpression also differed by sex; P53 overexpression was more frequent in males and intestinal-type GC patients. In our previous report on P53 overexpression, the clinical and prognostic significance differed by histological type of GC; P53 overexpression was more common in intestinal-type GC, but was associated with a poor prognosis for diffuse-type GC[ 18 ]. Therefore, it is also likely to act as a factor that affects GC prognosis differently in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis of the intestinal barrier is also disturbed by an imbalance that occurs between pro- and anti-apoptotic genes. In particular, it has been demonstrated that the p53 gene is involved in the initiation of the apoptosis mechanisms of the cellular cycle and its overexpression has been associated with different types of intestinal cancer [ 44 , 45 ]. Moreover, tumor suppressor p53 regulates the anti-apoptotic (Bcl2) and pro-apoptotic (Bax) members of the Bcl-2 proteins family, which control apoptosis by monitoring mitochondrial outer membrane permeabilization [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the effects of Helicobacter pylori eradication treatment, p53 overexpression, and incidence of metachronous GC in this cohort. 6 , 7 ) The following patients were excluded from the present study: those with incomplete medical records or unclassified histology, those who were lost to follow-up, those with a prior history of other cancers at the time of diagnosis, and those with other inoperable diseases. Finally, we included 2,983 patients in the analysis and classified them into three groups based on age: I (young, age <65 years, n=1,680), II (early old, age 60–74 years, n=919), and III (old, age ≥75 years, n=384) ( Fig.…”
Section: Methodsmentioning
confidence: 99%